Potret LHKPN dan LPPDK dalam Pemilihan Gubernur dan Wakil Gubernur di Provinsi Jawa Barat dan Jawa Timur Tahun 2018 untuk Mewujudkan Pemilu Berintegritas - Nurlia Dian Paramita (Badan Pengawas Pemilihan Umum, 2020)
Report of State Official Assets (LHKPN) becomes one of the evidences for the amount of financial ownership owned by candidates for head and deputy regional head. This report is submitted as an effort to ensure data transparency and to prevent potential out-of-bounds money circulation during the campaign period. Law 10 of 2016 requires all participants in the head and deputy regional head elections to report the final financing results of activities in the campaign fund stage, namely Report of Receipt and Expenditure of Campaign Funds (LPPDK). Both report formats lead to the creation of elections with integrity. LHKPN does not have a standard assessment of the accuracy of assets owned by regional head candidates. The LPPDK as the final accountability report can only be reviewed from the results of the audit report announced by the KPU. Using a qualitative method, this paper is intended to explain the validity of the model as an instrumentation to create a fair election as well as to convey ideas about a more credible campaign funding reporting for the next local election.